Governing Islamic Marriage: The Role of Tawkil Wali Bil Kitabah in Indonesia’s Marriage Registration System - Akhmad Shodikin; Adyananda Firnaz Asyifa; Jefik Zulfikar Hafizd; Dewi Safitri; Edy Setyawan (UIN Sunan Gunung Djati, 2026)
This article examines Tawkil Wali bil Kitabah as a legal-administrative instrument through which the state governs Islamic marriage within Indonesia’s marriage registration system. The study addresses the tension between classical fiqh munakahat requirements, particularly the presence of a marriage guardian, and contemporary social realities marked by mobility and administrative demands. This research is primarily framed as normative-doctrinal legal research with a descriptive-analytical approach, supported by an analysis of statutory regulations, marriage registration guidelines, and relevant scholarship on Islamic family law, as well as limited field-based information from Kantor Urusan Agama (Office of Religious Affairs, KUA) practice in Cirebon as an illustrative example. The findings show that Tawkil Wali bil Kitabah functions not merely as an administrative formality but as a state-recognized legal instrument that standardizes the delegation of guardianship authority, ensures procedural order, and strengthens legal certainty in Islamic marriage. The study also shows that this mechanism reflects the harmonization of fiqh, the Compilation of Islamic Law, and state administrative practice in the governance of marriage. It concludes that Tawkil Wali bil Kitabah represents an evolving model of governing Islamic marriage in Indonesia, in which religious norms are operationalized through legal-administrative procedures without displacing their normative foundations.